MOTIVASI PEGAWAI DALAM MENGEMBANGKAN PESANTREN - Lita Gunawati (Universitas Negeri Jakarta, 2014)
The objective of this research is to gain a deep understanding of the motivation employee in developing boarding school at Fajar Dunia. This research is a case study method. The validity of qualitative data obtained through the extension of time doing research and triangulation of data collection techniques and data sources in the field. The result show: 1). Goal setting in Fajar Dunia Boarding School began from making vision and mission through the challenging and specific goal to improve individual and job performance. To make it sure, superior always giving feedback to subordinates to know that the things is on the track to reach the goal. 2) Empowerment was done with formally program such training to improve self actualization, beside that the greater autonomy always be given to subordinates with many cases such sharing power and belief, making decision, and provide the tools so that the employee can more fully use their potential, thus satisfying higher-level for achievement, recognition, and self-actualization 3) Reward include extrinsic and intrinsic. Extrinsic reward are given by a manager such pay increases, bonuses, incentive, etc, with equitable system and related to a specific level of job performance. Intrinsic reward are the satisfactions an employee receives in the process of performing a particular action such completion, and achievement. Both of thus rewards are a potential barrier to work motivation in receiving organizational goal